Operating a reservoir system based on the shark machine learning algorithm - Allawi M.F. (Springer Verlag, 2023)
Artificial intelligence; Decision making; Genetic algorithms; Learning systems; Reliability analysis; Reservoirs (water); Stochastic systems; Comprehensive analysis; High dams; Mathematical optimization model; Performance indicators; Semi-arid region; Stochastic features; Water deficits; Water release; Learning algorithms; algorithm; machine learning; model; numerical model; optimization; performance assessment; reservoir; semiarid region; stochasticity; water demand; water stress; Aswan Dam; Aswan [Egypt]; Egypt; Chondrichthyes